CRYPTOMEIGENIA SP. (DIPTERA: TACHINIDAE) COMO PARASITOIDE DE ADULTOS DE PHYLLOPHAGA (PHYTALUS) RUFOTESTACEA (MOSER, 1918) (COLEOPTERA: MELOLONTHIDAE) EN CHIAPAS, MÉXICO - Ramírez-Salinas, Concepción; Pacheco-Flores, Cutberto; Castro-Ramírez, Adriana E. (Instituto de Ecología, A.C., 2006)
A description is made of the biology and activity of Cryptomeigenia sp. (Diptera: Tachinidae), an endoparasitoid of Phyllophaga rufotestacea (Moser, 1918) (Coleoptera: Melolonthidae) adults. Phyllophaga rufotestacea specimens were collected from May to October in 2002 and from June to September in 2003 in agricultural and forested plots in southern San Cristobal de Las Casas, Chiapas, Mexico. The collections were performed three nights a week, between 1900 and 2130 h. Of the 1385 adult specimens collected in 2002, 564 were female and 821 male; 26.9% of the males were parasitized. Of the 1023 specimens collected in 2003, 25.17% of males and 15.58% of females were parasitized. In 2003, parasitism by Cryptomeigenia sp. was shown to occur throughout the flying period of P. rufotestacea (June 9 to September 8), although the percentage of infected individuals varied during this period (from cero to 38.7%). Laboratory study showed that Cryptomeigenia sp. has four development stages: egg, larva, pupa and adult. Under laboratory conditions the first stages occur in P. rufotestacea beetles over a period of 29-32 days. Cryptomeigenia sp. oviposits anywhere between one and 45 eggs in a male or female beetle’s abdominal cavity, where the eggs develop and eclose. A number of larvae hatch though only one survives. This larva becomes the sole survivor by eating the other, smaller larvae and the host’s organs, which causes host death. This parasite is specific to P. rufotestacea adults. Over 12 Melolonthidae species are found at the same site and do not parasitize this potential host.